Anthropometric and functional indicators of athletes with different types of body constitution - Serhii Holiaka; Ivan Hluhov (Kharkiv State Academy of Physical Culture, 2018)
Purpose: to determine the main anthropometric indicators, the level of the functional state of the cardiovascular and respiratory systems of athletes, depending on the type of constitution of their body. Material & Methods: in the course of the study, measurements were made of the type of body constitution, morphological indicators and indicators of the functional state of the cardiovascular and respiratory systems of athletes. Two experimental groups were formed from specialized sport school athletes. Results: the analysis of anthropometric and functional indicators of the cardiovascular and respiratory systems of athletes specializing in freestyle wrestling and rowing from specialized sport school is carried out. The dependence of the state of morphological and functional parameters of athletes depending on the type of body constitution is shown. Conclusion: the dependence is established between the type of body constitution with the morphological and functional indicators of athletes specializing in freestyle wrestling and canoeing.